An integrated workflow to design screen/slotted liners in geothermal wells. (March 2018) - Yang, Ruiyue; Huang, Zhongwei; Li, Gensheng; Shi, Huaizhong; Song, Xianzhi; Shi, Yu
Highlights: An integrated workflow which complementarily utilizes analytical and numerical. Methods to design screen/slotted liners in geothermal wells is presented. Prediction of critical temperature for plastic deformation is significant in the safe design of the screen/slotted liners in geothermal wells. A selection guide for the schematic of holes/slots configuration is provided. Abstract: Screen/slotted liners can be used in geothermal well completions. However, the thermally-induced stress caused by elevated temperature could substantially deteriorate the collapse strength. This paper presents an integrated workflow which complementarily utilizes analytical and numerical methods to design screen/slotted liners in geothermal wells. The collapse rating of a screen/slotted liner is obtained by a modified analytical approach. The thermally-induced stress is estimated through the Finite Element Method Subsequently, the collapse strength assessment for a screen/slotted liner when subjected to high-temperature is made by combining these two approaches. Finally, a selection guide for the schematic of holes/slots configuration is provided. The result depicts that high-temperature could substantially impair the collapse strength of a screen/slotted liner. It also suggests that prediction of the critical temperature for plastic deformation is important in the safe design of the screen/slotted liners in geothermal wells. The method is simple and versatile, without complicated mechanical-thermo-coupling process. It can provide a guidance for completion engineers to modify the design of screen/slotted liners prior to the actual treatment in geothermal wells.